RESPON PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascaloniacum L.) TERHADAP PEMBERIAN PUPUK ANORGANIK DAN PUPUK ORGANIK - Siti Hawa Wasaraka; rosmala widijastuti; Diana S Susanti; Mariana L Resubun (Musamus University, 2022)
ABSTRACT Shallot (Allium ascalonicum L.) is a horticultural commodity that is consumed by many people. This study aims to obtain the right combination of inorganic and organic fertilizer treatments for the growth and production of shallots .this research was conducted in Isano Mbias village, Tanah miring District, Merauke Regency, from June to Agustus 2018 using a randomized design group (RBD) of one factor, namely the dose of inorganic and organic fertilizer with 5 treatment levels, namely (P1) 100% Inorganic;(P2) 75% Inorganic +25% Organic ; (P3) 50% Inorganic + 50% Organic (P4) 25% Inorganic +75% Organic (P50) 100% Organic. Based on the research results of the combination treatment of inorganic fertilizers and organic fertilizers, the results did not significantly affect the parameters of the number of leaves, plant height, wet stover weight per clump, number of tubers per clump, we tuber weight per clump, and dry tuber weight per clump. Giving 50% inorganic +50% organic (P3) fertilizer gives the best results on the growth and production of shallot plants with a yield of 27.19 grams/family (13.96 tons /ha. Keyword: NPK phonska, ZA, KCL, Manjung cattle compost